The science and practice of workforce analytics: Introduction to the HRM special issue - Huselid, Mark A. (Human Resource Management, 2018)
This special issue of Human Resource Management is focused on the latest thinking, research, and practical advances in the emerging field of Workforce Analytics. The eight diverse papers in this issue present new theoretical developments, methodological and statistical tools, and examples of innovative workforce analytics in practice. Taken as a whole, the findings show that workforce analytics can significantly enhance the ability of leaders and managers to achieve their operational and strategic objectives through more effective workforce management. But capitalizing on these opportunities will require both HR and line managers to develop a comprehensive understanding of how the workforce contributes to their firm's strategic success—and this understanding must be reflected in the workforce metrics and analytics they develop and deploy.